Profiling of fatty acid metabolism in the dorsal root ganglion after peripheral nerve injury - Yamamoto, Shota; Hashidate-Yoshida, Tomomi; Shimizu, Takao; Shindou, Hideo (Frontiers in Pain Research, 2022)
Peripheral nerve injury (PNI) induces neuronal hyperexcitability, which underlies neuropathic pain. The emergence of RNA sequencing technologies has enabled profiling of transcriptional changes in pathological conditions. However, these approaches do not provide information regarding metabolites such as lipids that are not directly encoded by genes. Fatty acids (FAs) are some of the essential lipids in mammalian organisms and are mainly stored as membrane phospholipids. In response to various biological stimuli, FAs are rapidly released and converted into several mediators, such as eicosanoids and docosanoids. FAs themselves or their metabolites play important roles in physiology and pathology. In this study, using a comprehensive lipidomic analysis of FA metabolites, 152 species were measured in the dorsal root ganglia of mice at multiple time points after PNI. We found that PNI increased the ω-6 FA metabolites produced by cyclooxygenases but not those produced by lipoxygenases or cytochrome P450 enzymes in the dorsal root ganglia. In contrast, ω-3 FA metabolites biosynthesized by any enzyme transiently increased after nerve injury. Overall, these findings provide a new resource and valuable insights into PNI pathologies, including pain and nerve regeneration.